ALIGN-CCUS: Results of the 18-month test with aqueous AMP/PZ solvent at the pilot plant at Niederaussem – solvent management, emissions and dynamic behavior. (July 2021) - Moser, Peter; Wiechers, Georg; Schmidt, Sandra; Monteiro, Juliana Garcia Moretz-Sohn; Goetheer, Earl; Charalambous, Charithea; Saleh, Ahmed; van der Spek, Mijndert; Garcia, Susana
Highlights: Continuous long-term testing with aqueous AMP/PZ (3 molar 2-Amino-2-methyl-1-propanol/1.5 molar piperazine) solvent over 12, 275 hours at a lignite-fired power plant. A minimum specific reboiler duty of 2, 970 MJ/tCO2 was identified (operation with four active absorber beds and intercooling (40°C). Tests with CO2 capture rates between 90 and 98% showed only a small increase of the specific energy demand at 95% (+20 MJ/tCO2). The average solvent consumption during 400 days of operation was 0.45 kg/tCO2 and the solvent shows a slow-progressing linear degradation behavior. Performance tests of several emission mitigation measures have been carried out: single water wash, double water wash, acid wash, dry bed, wet electric precipitator and flue gas pre-treatment. Abstract: After a 13, 000-hour test campaign with aqueous 30 wt% MEA (2-aminoethanol) solvent at the CO2 capture pilot plant at Niederaussem, another long-term test was carried out as part of the ALIGN-CCUS project. This test ran for more than 12, 275 hours with aqueous AMP/PZ (2-Amino-2-methyl-1-propanol/piperazine) solvent, named CESAR1 (3.0 molar AMP (~26.74 wt%) and 1.5 molar PZ (~12.92 wt. %)). A minimum specific reboiler duty of 2, 970 MJ/tCO2 was identified for the capture plant operation with four active absorber beds (total 16 m packing height) and intercooling (40°C). Neither a lower desorber pressure of 1.5 bar(a), instead of 1.75 bar(a), nor a change of the different positions of intercooling had a significant effect on energy consumption. Reduction of the active packing height to three beds (i.e., 12 m), resulted in a moderately higher specific energy demand (+100 MJ/tCO2 ). Tests with CO2 capture rates between 90 and 98% showed only a small increase of the specific energy demand at 95% (+20 MJ/tCO2 ) and four active packings (98%: +250 MJ/tCO2 ). The average solvent consumption of CESAR1 during 400 days of operation was 0.45 kg/tCO2 and is lower than for MEA if the phase of accelerated non-linear degradation of MEA is taken into account. CESAR1 follows a slow-progressing linear degradation behavior; neither a critical metal ion concentration threshold value could be found that triggers fast degradation nor a correlation between accumulated trace components or metal ion concentrations in the solvent and the degradation rate was observed. Highly transient tests were conducted to investigate the dynamic behavior of the capture plant and subsequently special settings were chosen to stimulate high emissions for the investigation of aerosol-based emissions, connected with performance tests of several emission mitigation measures: single water wash, double water wash, acid wash, dry bed, wet electric precipitator and flue gas pre-treatment. When applying the dry bed configuration, emissions of AMP between 15 - 20 mg/Nm 3, PZ between 3 - 7 mg/Nm 3, and NH3 below 3 mg/Nm 3 were achieved.